BNT162b2 Vaccination during Pregnancy Protects Both the Mother and Infant: Anti-SARS-CoV-2 S Antibodies Persistently Positive in an Infant at 6 Months of Age - Chetna Mangat; Natasa Milosavljevic (Case Reports in Pediatrics)
Vaccinations are the most important intervention for controlling the ongoing coronavirus disease (COVID-19) pandemic, caused by the SARS-CoV-2 virus. BNT162b2 is an mRNA-based vaccine, which is promising and safe for use during pregnancy, as it could help prevent SARS-CoV-2 infection and its complications during pregnancy. Other vaccines, such as influenza and Tdap (tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis) vaccines, provide significant protection for babies. Recent studies have shown that COVID-19 antibodies are present in newborns at birth, owing to maternal BNT162b2 vaccination during pregnancy; however, it is currently unclear how long these antibodies could protect infants from SARS-CoV-2 infection and its complications. Herein, we present the case of a preterm baby born at 33 weeks via an emergency cesarean section owing to maternal complications. The mother had received two doses of the BNT162b2 vaccine at 22 and 26 weeks of gestation. Positive anti-SARS-CoV-2 S antibodies were detected in the infant at 2 weeks, 6 weeks, 3 months, and 6 months of age. This is the first case report in which BNT162b2 vaccination during pregnancy yielded a persistent immune response in an infant at 6 months of age. The declining anti-SARS-CoV-2 S antibody titers noted at 6 months of age emphasize the need for the vaccination of children at this age.